Analisa Pola Gadai BPKB Kendaraan dengan Menerapkan Algoritma FG-Growth - Ningsih, Fitri Pratiwi (TIN: Terapan Informatika Nusantara, 2021)
Data Mining is a series of processes to explore added value in the form of information that has been known manually from a database by extracting patterns from data with the aim of manipulating data into more valuable information obtained by extracting and recognizing patterns important or interesting from the data contained in the database. The data mining technique has various algorithms and techniques for solving problems related to data, one of which is the FP-Growth algorithm and the technique of association rules. Information displayed using association rules technique, which displays the value of support and confidence from each data mining process. With the FP-Growth algorithm, it is evident from the results of the tests carried out, the FP Growth algorithm and association rules technique run as expected and can be implemented in this Data Mining.